2002
DOI: 10.1097/00126334-200207010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adherence to HIV Protease Inhibitors: Comparison and Combination of Various Methods, Including MEMS (Electronic Monitoring), Patient and Nurse Report, and Therapeutic Drug Monitoring

Abstract: Diary-corrected MEMS data gave a detailed insight into patients' adherence patterns. Patients' self-report and therapeutic drug monitoring were significantly correlated with the MEMS data, and the clinical nurse specialist may also play a role in identifying patients who are imperfectly adherent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…In our study, self-reported missed cART doses in a 7-day recall period varied widely across CCASAnet sites, ranging from 1.6% in Mexico to 33.0% in Honduras. Although there are several methods for measuring adherence, and self-reported measures may overestimate the use of medication compared to microelectronic devices(7,36), our study shows an association between self-reported missed cART doses and a lower probability of viral suppression. These findings further support the use of the RST as a reliable measure of adherence that may be incorporated into routine clinical care(19).…”
Section: Discussionmentioning
confidence: 61%
“…In our study, self-reported missed cART doses in a 7-day recall period varied widely across CCASAnet sites, ranging from 1.6% in Mexico to 33.0% in Honduras. Although there are several methods for measuring adherence, and self-reported measures may overestimate the use of medication compared to microelectronic devices(7,36), our study shows an association between self-reported missed cART doses and a lower probability of viral suppression. These findings further support the use of the RST as a reliable measure of adherence that may be incorporated into routine clinical care(19).…”
Section: Discussionmentioning
confidence: 61%
“…Adherence measured electronically is consistently more closely associated with HIV-1 RNA than are other methods (48, 49). In research, EDMs have been the measurement method of choice (50, 51). Unfortunately, these technologies are currently impractical outside of studies because they may be burdensome to patients and incompatible with adherence-promoting strategies, such as pill cases.…”
Section: Guidelinesmentioning
confidence: 99%
“…Adherence assessment by caregiver reports is commonly used in studies reporting ART among children and is consistently higher than adherence by other measures like pill count or pharmacy refill, suggesting that caregivers likely overestimate their child's adherence [12,13]. Electronic dose monitoring with technologies like Medication Event Monitoring Systems (MEMS ® ) – bottle caps fitted with a microchip that records the time and date of each bottle opening – is most consistently associated with virological outcomes [14,15] but is often too expensive for routine use in LMICs outside of research settings [16]. …”
Section: Introductionmentioning
confidence: 99%